2016
DOI: 10.1371/journal.pone.0151061
|View full text |Cite
|
Sign up to set email alerts
|

High-Density Lipoprotein-Associated miR-223 Is Altered after Diet-Induced Weight Loss in Overweight and Obese Males

Abstract: Background and AimsmicroRNAs (miRNAs) are small, endogenous non-coding RNAs that regulate metabolic processes, including obesity. The levels of circulating miRNAs are affected by metabolic changes in obesity, as well as in diet-induced weight loss. Circulating miRNAs are transported by high-density lipoproteins (HDL) but the regulation of HDL-associated miRNAs after diet-induced weight loss has not been studied. We aim to determine if HDL-associated miR-16, miR-17, miR-126, miR-222 and miR-223 levels are alter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
42
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(48 citation statements)
references
References 25 publications
3
42
3
Order By: Relevance
“…Some studies reported that the contents of miR-486 and miR-92a in HDL are reduced in vulnerable CVD patients [68]. HDL-associated miR-223 levels are decreased after high-protein diet-induced weight loss in overweight and obese males [69]. Intestinal lymphatic HDL-associated miR-223 is reduced during insulin resistance and is restored by niacin in rats [70].…”
Section: Micrornas (Mirnas) In Hdlmentioning
confidence: 99%
“…Some studies reported that the contents of miR-486 and miR-92a in HDL are reduced in vulnerable CVD patients [68]. HDL-associated miR-223 levels are decreased after high-protein diet-induced weight loss in overweight and obese males [69]. Intestinal lymphatic HDL-associated miR-223 is reduced during insulin resistance and is restored by niacin in rats [70].…”
Section: Micrornas (Mirnas) In Hdlmentioning
confidence: 99%
“…For example, in a study where the most abundant miRNA transported by HDL, miR-223 (up to 10,000 copies per microgram of HDL), was transported to Huh7 cells showed a significant reduction of miR-223 target gene expression (Vickers et al, 2011). In addition to that, in this review, two studies (Niculescu et al, 2015;Tabet et al, 2016) involving human samples also shown evidence for miRNA transportation via HDL.…”
Section: High-density Lipoprotein (Hdl)mentioning
confidence: 60%
“…A biomarker can thus provide impartial information regarding the current physiological state of living organisms (Gill et al, 2017). Biomarkers exist in the form of antibodies (Dardari et al, 2000: IgG-ZEBRA as a biomarker in young patients with nasopharyngeal carcinoma), microbes (Shah et al, 2018: the fecal microbiome as a biomarker of colorectal cancer), DNA (Teo et al, 2019: sequencing of circulating cell-free DNA [cfDNA] from human blood plasma as a noninvasive methodology to study age-associated changes in the epigenome in vivo), RNA/miRNA (as tabulated in this review), lipids (Seow et al, 2019: the lipid fraction of the solid nonenhancing region showed potential as a novel prognostic biomarker of survival outcome in glioma), metabolites [Lou et al, 2019: a urinary metabolite of polycyclic aromatic hydrocarbons, 8hydroxy-2′-deoxyguanosine (8-OHdG), can be a biomarker of oxidative stress in pregnant women], and/or protein [Xu et al, 2019: serum protein, the insulin-like growth factor-binding protein miR-19, miR-21, miR-132, miR-133, miR-146, miR-155, miR-223, miR-377, miR-451, miR-641, miR-887, miR-1246, and miR-4284 CAD miRNAs were associated with MP-containing plasma compared to MP-free plasma of CAD patients Tabet et al, 2016 HDL -serum PEG-6000 method Qiazol miRNA-easy kits f Weight loss Downregulation in HP patient vs. normal protein diet miR-16 and According to previous study: downregulation in gastric bypass bariatric surgery patients -548c-5p, miR-638, miR-5787, miR-8975, and miR-6869-5p Involved in the process of glucose metabolism in CRC Ostenfeld et al, 2016 Pooled (IGFBP-1), as a biomarker for the early detection of gastrointestinal cancer]. Alteration in biomarker concentration, structure, function, or action can be associated with the onset, progression, or even regression of a particular disorder as a result of how the body responds to it (Gill et al, 2017).…”
mentioning
confidence: 99%
“…Tabet et al showed a mild decrease in HDL-carried miR-223-3p concentration following a 12-week diet rich in proteins and that this change in HDL-miR-223-3p level was associated with a diet-induced weight loss in overweight and obese men (Table 3) [137]. Our group reported an increased concentration of HDL-carried miR-223-3p and miR-135a-3p, which was associated with an overall worsening of the cardiovascular disease (CVD) risk profile (e.g.…”
Section: Hdl-carried Mirna Concentration Is Affected By the Dietmentioning
confidence: 99%